Effect of Sn substitution at Sb site on the magnetic properties of Mn2NiSb full-Heusler alloy - Govind B.; Bharti P.; Kumar A.; Bano S.; Singh S.; Awana V.P.S. (My University, 2025)
Alignment of spin of Mn-Mn atoms in Heusler structure mainly depends upon the distance between them which can be easily manipulated by substituting the main group Z-elements in the Mn2-based full-Heusler alloys. In this article, we report the effect of Sn doping at the Sb site in the Mn2NiSb1−XSnX (0.02≤x≤0.1) full-Heusler alloys. We have performed the X-Ray diffraction (XRD) measurement of each sample to obtain the structural information of the synthesized full-Heusler phase. Rietveld refinement performed on the each XRD data of Mn2NiSb1−XSnX (0.02≤x≤0.1) revealed that all the samples were crystallized in the Hg2CuTi prototype (Space group-Fm3m) structure. Analysis of selected area diffraction (SAED) pattern obtained from transmission electron microscopy (TEM) measurement revealed that a single phase of full-Heusler was obtained for the highest Sn content (x = 0.1) sample. Magnetization variation with applied magnetic field plot exhibited the ferromagnetic ground state of each sample as evidenced from hysteresis loop and saturation was obtained up to 1.0 Tesla field. Zero field cooled (ZFC) and field cooled (FC) measurements were also investigated and splitting between ZFC and FC were found to be increasing with an increase in the Sn content. This increment in ZFC and FC splitting with Sn content was attributed to the coupling between the ferrimagnetic (FIM) nature of Mn2NiSn phase with ferromagnetic (FM) nature of Mn2NiSb phase at the interfaces. Small shifting of hysteresis curve observed in the virgin M-H loop around the origin also indicated the spontaneous exchange biasing due to the FM/FIM interaction. Compensation of magnetization followed by exchange biasing with two magnetic phase (FM/FIM) governed by the controlled doping of Sn in Mn2NiSb have been alluringly elaborated. Direct interaction between different known magnetic phases/sub-lattices are rarely investigated which can be used to make suitable materials for spintronic application such as magneto resistive read heads and sensors. © 2022 Elsevier B.V.